2013
DOI: 10.3852/12-125
|View full text |Cite
|
Sign up to set email alerts
|

Neozygites osornensis sp. nov., a fungal species causing mortality to the cypress aphid Cinara cupressi in Chile

Abstract: An entomophthoralean fungus causing epizootics in populations of the cypress aphid, Cinara cupressi Buckton, in Chile is described as a new species, Neozygites osornensis Montalva et Barta. The aphid pathogen is described based on morphological characters. An exhaustive description, illustrations and a comparison with closely related species are provided. The fungus differs from similar Neozygites species by smaller hyphal bodies, nuclei, primary conidia, capilliconidia and capilliphores and by noticeably diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We retrieved the Worldclim2 bioclimatic variables (Fick and Hijmans, 2017) with a spatial resolution of ca.1 km 2 . The occurrence dataset for all TES was extracted from the Global Biodiversity Information Facility (GBIF, 2018) and previous studies (Baldini et al, 2008;Retamal et al, 2013;Ruiz et al, 2014) (for details, refer to Table S1). We considered a global niche (fundamental niche) approach, aiming to generate a pessimistic prediction of all the climatic conditions under which the species can occur (Gallien et al, 2012); also, the lack of national occurrences for some species could generate a sub estimation of some ES (Pauchard et al, 2011).…”
Section: Current Geographic Distributionsmentioning
confidence: 99%
“…We retrieved the Worldclim2 bioclimatic variables (Fick and Hijmans, 2017) with a spatial resolution of ca.1 km 2 . The occurrence dataset for all TES was extracted from the Global Biodiversity Information Facility (GBIF, 2018) and previous studies (Baldini et al, 2008;Retamal et al, 2013;Ruiz et al, 2014) (for details, refer to Table S1). We considered a global niche (fundamental niche) approach, aiming to generate a pessimistic prediction of all the climatic conditions under which the species can occur (Gallien et al, 2012); also, the lack of national occurrences for some species could generate a sub estimation of some ES (Pauchard et al, 2011).…”
Section: Current Geographic Distributionsmentioning
confidence: 99%
“…A survey of entomopathogenic fungi of C. cupressi , was carried out in southern Chile (project DID 2011-11) between 2007 and 2013. Several strains of Lecanicillium attenuatum were isolated and a Neozygites species wasreported from naturally infected C. cupressi cadavers (Figure 1) in different localities [17,101]. Several laboratory studies around the world demonstrated high levels of mortality in C. cupressi with entomopathogenic fungi of the order Hypocreales, especially with Lecanicillium sp.…”
Section: Microbial Control Of Invasive Pests With Entomopathogenicmentioning
confidence: 99%
“…However, field efficacy varies considerably as these fungi are strongly influenced by the environmental conditions such as humidity and temperature. On the other hand, some fungi of the order Neozygitales were cited and collected in different locations in Chile [101,105,106]. For example, Neozygites turbinata (Kenneth) Remaudière and Keller and Neozygites osornensis Montalva and Barta are highly specific to certain aphids and can cause epizootics in pest populations, and they can also be multiplied as protoplasts or hyphal bodies.…”
Section: Microbial Control Of Invasive Pests With Entomopathogenicmentioning
confidence: 99%